Koneksi Antar Destinasi bagi Peningkatan Pendapatan Asli Daerah di Kabupaten Sambas - Erdi; Sukamto; Padilah, Ahirul Habib (Journal of Social and Policy Issues, 2023)
One source of regional income that has the potential to be developed  is the tourism sector. Currently, the central government is also focusing on promoting tourism  as a potential source of economic growth. When the regions do this, it will become a synergy with central policy. National and regional economic development through tourism is believed  to contribute to income. This research uses a descriptive qualitative research method with three main studies namely library research, field studies and documentation research with 5 (five) informants, namely sub-district heads, village heads, traditional leaders and administrators, business actors, and The community at the destination. The Results where the destination has no significant impact on regional revenue from this sector. As if it read only hotels and restaurants contribute to local revenue. Therefore, this conclusion is unfair. Therefore, each region is required to be able to explore and manage its tourism potential as a  source of income to finance regional expenditures. Sambas Regency as one of the regencies in  West Kalimantan Province; has potential tourism resources that are known not only for the  beauty and uniqueness of nature, but also for fame as a beautiful area at the end of the country.  The conclusion isThe local government of Sambas Regency is still unable to catch them opportunities to attract PAD from tourist activities because until recently, these opportunities were missed never realized.